2019
DOI: 10.1093/humrep/dez122
|View full text |Cite|
|
Sign up to set email alerts
|

Anogenital distance in children born of mothers with polycystic ovary syndrome: the Odense Child Cohort

Abstract: STUDY QUESTION Are higher testosterone levels during pregnancy in women with polycystic ovary syndrome (PCOS) associated with longer offspring anogenital distance (AGD)? SUMMARY ANSWER AGD was similar in 3-month-old children born of mothers with PCOS compared to controls. WHAT IS KNOWN ALREADY AGD is considered a marker of prenatal androgenization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Women with PCOS have significantly longer AGDs than unaffected controls (Table 1 ), supporting the hypothesis that PCOS involves elevated prenatal exposure to testosterone (Filippou & Homburg, 2017 ). Daughters of mothers with PCOS also demonstrate evidence of longer AGDs than daughters of unaffected women (Barrett et al, 2018 ; Perlman et al, 2020 , but see Glintborg et al, 2019 ), in association with high serum testosterone in affected mothers during gestation. Clinical characteristics of PCOS, including elevated serum testosterone and increased ovarian follicle count, are also positively associated with AGD in nonclinical samples of female college students (Mendiola et al, 2012 ; Mira‐Escolano et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Women with PCOS have significantly longer AGDs than unaffected controls (Table 1 ), supporting the hypothesis that PCOS involves elevated prenatal exposure to testosterone (Filippou & Homburg, 2017 ). Daughters of mothers with PCOS also demonstrate evidence of longer AGDs than daughters of unaffected women (Barrett et al, 2018 ; Perlman et al, 2020 , but see Glintborg et al, 2019 ), in association with high serum testosterone in affected mothers during gestation. Clinical characteristics of PCOS, including elevated serum testosterone and increased ovarian follicle count, are also positively associated with AGD in nonclinical samples of female college students (Mendiola et al, 2012 ; Mira‐Escolano et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data derived from different study groups and the potential role of androgen in the pathophysiology of the disease has strong foundations. However, a recent Danish study (43) did not find an association between higher maternal testosterone levels and longer AGD in the offspring, questioning the impact of prenatal hormonal exposure on AGD length.…”
Section: Discussionmentioning
confidence: 92%
“…Further, 74 women were pregnant more than once within the inclusion period, and only the first pregnancy was included in the data set. Maternal age, pre-pregnancy body mass index (BMI), and parity were collected Health Foundation (Helsefonden), The National Board of Social Services, and Lundbeckfonden (F-61171- [19][20][21][22][23][24][25][26][27].…”
Section: Study Populationmentioning
confidence: 99%
“…18 We previously reported comparable AGD length in women with PCOS compared with controls; however, maternal testosterone was an independent positive predictor of offspring AGD in boys. 19 These findings suggested that boys could be more susceptible to maternal testosterone exposure than girls. 19 To our knowledge, associations between offspring AGD and risk of ADHD have not been investigated in human studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation